Inovasi Pengolahan Sampah: Mengubah Sampah Anorganik Menjadi Eco Brick di Desa Tosari - Ayyu Lailuki Azma; Oky Tania Savitri; Berlyana Andriani; Puspita Anggraeni; Kukuh Sinduwiatmo (CV. ITTC INDONESIA, 2024)
Indonesia is the second largest producer of plastic waste in the world. Plastic waste decomposes 4.444 times or approximately 1,000 years. Plastic waste has a negative impact on the environment, including accumulation of rubbish and other environmental pollution. Precautions are needed to overcome this problem. One of the right strategies is: 3R, namely Reduce, Reuse, Recycle, must be applied in dealing with plastic waste. However, not all locations have waste disposal facilities. Trash dumps are a necessity, especially nowadays. This is why we need landfills. The solution to this problem is to process inorganic waste into ecobricks. The aim of this service is to increase public awareness, especially in Tosari Village, Tosari District, Pasuruan Regency. Ecobricks have a positive impact on society by reducing plastic waste and turning it into usable goods, such as making study tables from ecobricks which can be used for learning at TPQ Roudlotul Qur'an.